From Policy to Practice: Inclusive Career Management in Higher Education - Siti Nur Aviatun Hasanah; Rifka Jannatul Firdausiah; Maulidatul Adzimah; Unzilah Khomairohtusshiyamah; Akmal Mundiri; Zohaib Hassan Zain (Al-Qalam Institute, 2026)
Inclusive career management has become a strategic priority in higher education policies, yet its practical implementation remains uneven. This study aims to examine how inclusive career management policies are translated into practice within higher education institutions and to identify factors influencing their effectiveness. Using a qualitative multi-site case study approach, data were collected from career center managers, faculty members, and students across several public and private universities through semi-structured interviews, document analysis, and observational data. The findings reveal three key patterns. First, institutional policies emphasizing inclusivity are largely implemented at an administrative level, with limited responsiveness to the concrete needs of students with disabilities and those from low socioeconomic backgrounds. Second, career guidance services predominantly adopt standardized models, although emerging practices show a gradual shift toward personalized and competency-based approaches. Third, universities demonstrating effective inclusive career management exhibit strong cross-stakeholder collaboration involving career centers, academic units, industry partners, and government agencies. This study contributes empirical evidence on the policy–practice gap in inclusive career management and highlights collaborative governance as a critical enabler. The findings suggest the need for data-driven personalization and integrated stakeholder engagement to ensure equitable career development outcomes in higher education.